The perceptions of patients on antiretroviral therapy (ART) and treatment supporters with regard to their role towards ART adherence, at ART clinics in the intermediate hospital Oshakati, Namibia - Tuhadeleni, Olivia Ningeninawa; Lukolo, Linda Ndeshipandula (International Journal of Medicine, 2017)
Background: The benefits of antiretroviral therapy (ART) are undeniable: decreased morbidity and mortality, improved clinical outcomes, and decreased HIV transmission. In recent years, there have been remarkable efforts to roll out HIV support and treatment programs, resulting in ART access to nearly 4 million people in sub-Saharan Africa. However, a decisive step in improving outcomes of these programs relies on ART adherence. This study was conducted by aiming at exploring and describing the perceptions of patients on ART and treatment supporters about their roles in ART adherence. It was carried out at Oshakati ART clinic in the Intermediate Hospital Oshakati in Oshana region, Northern Namibia.Methods: The qualitative investigation was carried out on patients on ART and treatment supporters by means of unstructured interviews through convenient sampling technique. The data were analysed by content analytical method.Results: The study results from all respondents were consolidated, which gave a clear understanding regarding adherence at the ART clinic in Intermediate Hospital Oshakati. The perceptions of patients on ART and treatment supporters with regard to their role towards ART adherence were classified based on participants’ experiences into two main themes and sub-themes, including: 1) ART patients’ perceptions around their current roles in ART adherence comprise of four sub-themes of ART patients’ perceptions about taking medication daily, perceptions about collection of medicine supply and follow-up visits, perceptions about food and medication and perceptions about support in ART treatment; 2) Treatment supporters’ perceptions about their role in ART adherence consist of four sub-themes of perceptions about follow-up visits and collection of medicine, perceptions about psychosocial and emotional support, perceptions about giving food and medication and perceptions about encouraging personal hygiene.Conclusion: Patients and treatment supporters perceived adherence as an important aspect in the success of antiretroviral treatment. Giving patients correct information, personal motivation, patients understanding of treatment, traditional and religious beliefs were among other factors perceived by treatment supporters to be impacting on ART adherence.